Professional development and teacher collaboration: Analyzing tensions and fractures between theory and practice in a Spanish context - Trillo Alonso, Felipe; Nieto Cano, José Miguel; Martínez Domínguez, Begoña; Escudero Muñoz, Juan Manuel (Education Policy Analysis Archives, 2017)
This article analyzes teaching collaboration, one of the most promising professional development activities, as it appears in a broader investigation about different dimensions of continuing education of teachers in Spain. First, we describe the relevance of teaching collaboration as a new paradigm in professional development, and we present the conceptual definition of teaching collaboration and clarify key factors that explain current fractures between theory and practice. Our research questions, mixed investigation design (quantitative and qualitative) applied to a sample of teachers and Teacher Centers in different regions of the country, and data analysis and discussion focus on how and why good approaches (i.e. teachers collegiality in schools) fail to get developed or meet expectations, and theoretical and practical implications of these developments.